Prominent alumni: Dato' Sri Hajah Rohani Abdul Karim / Enabella Tasha Dennis ... [et al.] - Dennis, Enabella Tasha; Juman, Juliet Cheria; Abdul Khalik, Khairunisa; Nyareng, Rasiba (2023)
She was born on 3 January 1955 in Simanggang (now known as Sri Aman), Sarawak. She received her early education at SMK Methodist, Sibu. She has continued her education at Universiti Pertanian Malaysia in the field of agroindustry. She then resumed her studies until she obtained her Master of Business Administration (MBA) from Ohio University, Athens, USA. She has three children.